Anemia in Pregnancy as a Predisposing Factor of Severe Preeclampsia: Anemia dalam Kehamilan sebagai Salah Satu Faktor Predisposisi Preeklamsia Berat - Daliman; Gagah B.A. Nugraha; Prakosa J. Prasetyo (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: This case may partly explain that anaemia can be a predisposing factor for the development of many women with preeclampsia were have a low level of haemoglobin during their pregnancy.Methods: A case reportCase: We present a case 23-year-old pregnant woman who has had moderate anaemia with severe preeclampsia at 38-week pregnant. As the evidence, there were elevated blood pressure, decreasing haemoglobin obtained by routine blood analysis, and presence of urine protein by urinalysis examination.Conclusion: In terms of anaemia as one of a predisposing factor of preeclampsia it is important to care provider, pregnant women, and families to prevent anaemia in pregnancy through routine ANC.Keywords: anaemia, pregnancy, severe preeclampsia. Abstrak Tujuan: Kasus ini sebagian dapat menjelaskan bahwa anemia dapat menjadi faktor predisposisi bagi perkembangan banyak perempuan dengan preeklamsia yang memiliki kadar hemoglobin yang rendah selama masa kehamilan mereka.Metode: Laporan kasus.Kasus : Kami melaporan kasus ibu hamil berusia 23 tahun yang mengalami anemia sedang dengan preeklamsia berat di usia 38 minggu, dibuktikan dari peningkatan tekanan darah, penurunan hemoglobin, serta protein uria pada pemeriksaan urinalisis.Kesimpulan : Berkaitan antara anemia sebagai predisposisi preekalmsia, penting bagi petugas kesehatan dan ibu hamil serta keluarga untuk mencegah anemia dalam kehamilan melalui ANC yang rutin.Kata kunci : anemia, kehamilan, preeklamsia berat.